Sambucus nigra: A traditional medicine effective in reducing inflammation in mice. (30th January 2022) - Santin, José Roberto; Benvenutti, Larissa; Broering, Milena Fronza; Nunes, Roberta; Goldoni, Fernanda Capitanio; Patel, Yasmin Beatrisse Klein; de Souza, Jade André; Kopp, Mainara Adriane Tesser; de Souza, Priscila; da Silva, Rita de Cássia Vilhena; Pastor, Maria Verônica Dávila; de Souza, Angelita Boldieri; et al.
Abstract: Ethnopharmacological relevance: Sambucus nigra L. is a plant of European origin and popularly known as elder, elderberry, black elder, European elder, European elderberry, and European black elderberry, being described in pharmacopoeia of several countries. Its flowers and berries have been used in folk medicine to treat feverish conditions, coughing, nasal congestion, and influenza besides its popular use as anti-inflammatory, analgesic, and diuretic agent. Aim of the study: The aim of this investigation was to elucidate the anti-inflammatory and the relaxant effect of the lyophilized aqueous extract obtained from S. nigra 's flowers on in vivo and in vitro inflammation assays and on the isolated rat vascular and airway smooth muscle tissue. Material and methods: The anti-inflammatory activity of the extract was investigated using carrageenan-induced inflammation model in the subcutaneous tissue of male Swiss mice orally treated with S. nigra extract (30, 100, 300 or 600 mg/kg). Leukocyte influx and the secretion of chemical mediators were quantified in the inflamed exudate. Additionally, histological analysis of the pouches was performed. N-Formyl-methionine-leucine-phenylalanine-induced chemotaxis, lipopolysaccharide-induced TNF, IL-6, IL-1β, IL-10 and NO production, and adhesion molecule expression (CD62L, CD49d and CD18, flow cytometry) were analyzed in vitro using oyster glycogen-recruited peritoneal neutrophils or macrophages (RAW 264.7) stimulated with LPS and treated with the extract (1, 10 or 100 μg/mL). The resolution of inflammation was accessed by efferocytosis assay, and the antinociceptive activity was investigated using carrageenan-induced mechanical hypersensitivity. Finally, the effect of the extract was evaluated in isolated rat aorta and trachea rings. Results: The oral treatment with S. nigra promoted reduction in the neutrophil migration as well as the decrease of TNF, IL-1β and IL-6 levels in the inflamed exudate. In vitro treatment with S. nigra decreased NO2 −, TNF, IL-1β and IL-6 and promoted increase of IL-10 in LPS-stimulated neutrophils. Similarly, the extract reduced the NO2 −, TNF and IL-6 in LPS-stimulated macrophages. Rutin, the major constituent of S. nigra extract reduced NO2 −, TNF, IL-1β, and IL-6 and promoted the increase of IL-10 in LPS-stimulated neutrophils supernatant. The extract also shed CD62L and CD18 expressions. The extract was able to increase the efferocytosis of apoptotic neutrophils by increasing the IL-10 and decreasing the TNF levels. Additionally, the extract reduced the hypersensitivity induced by carrageenan and promoted a relaxant effect in isolated vascular and non-vascular rat tissue. Conclusions: S. nigra flowers extract presents anti-inflammatory effect by modulating macrophage and neutrophil functions including the production of inflammatory mediators and cell migration, by promoting efferocytosis and consequently the resolution of acute inflammation, besides exerting antinociceptive effects, scientifically proving its popular use as medicinal plant. Allied to the relaxant effect in both vascular and non-vascular smooth muscle tissue, S. nigra extract represents an important tool for the management of acute inflammation. Graphical abstract: Image 1